2007
DOI: 10.1177/1545968308315046
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Versus Activity-Dependent Fatigability in Patients With Central or Peripheral Motor Impairments

Abstract: In the rehabilitation literature, fatigue is a common symptom of patients with any neurological impairment when defined as a subjective lack of physical and mental energy that interferes with usual activities. Some complaints may, however, arise from fatigability , an objective decline in strength as routine use of muscle groups proceeds. By this refined definition of fatigue, exercise or sustained use reduces the ability of muscles to produce force or power, regardless of whether the task can be sustained. Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
78
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 33 publications
4
78
1
Order By: Relevance
“…While others have suggested that perceived fatigue and fatigability may not be closely related (62), this meta-analysis strengthens an inconsistent body of literature and provides directions for future research. The findings also add empirical support for the fatigue and fatigability model proposed by Kluger and colleagues, at least in the case of MS.…”
Section: Discussionsupporting
confidence: 54%
“…While others have suggested that perceived fatigue and fatigability may not be closely related (62), this meta-analysis strengthens an inconsistent body of literature and provides directions for future research. The findings also add empirical support for the fatigue and fatigability model proposed by Kluger and colleagues, at least in the case of MS.…”
Section: Discussionsupporting
confidence: 54%
“…Fatigability, which is the objective decline in strength after engaging a muscular group in actions normally performed [14], is characteristic of myasthenia, and, QMGS Items 8 8 as such, is an important feature to incorporate when assessing disease severity and change in myasthenia patients. The fact that endurance in MG patients improves after treatment supports this approach.…”
Section: Discussionmentioning
confidence: 99%
“…To date, research into muscle fatigue in people with MS has focussed on the neurophysiological aspects of activity-dependent fatigue induced by controlled muscle contractions [13]. These studies have found muscle fatigue is caused by deterioration in both central and peripheral neuromuscular function and is associated with slower gait speed and reduced cadence [14].…”
mentioning
confidence: 99%